Reflections on public enterprise and privatisation dawn to dusk - Ramanadham, Venkata Vemuri 1920- (New Delhi Vikas Pub. House, 1996)
Autobiographical account of an academician currently working as a specialist on public enterprise and privatization.
Keywords: Ramanadham, Venkata Vemuri -- 1920.; Government business enterprises; Privatization